Alkali-active red mud-based nanosphere modified fiber as well as preparation method and application thereof

By growing alkali-active red mud-based nanospheres on the surface of PVA fibers, the interface performance between the fiber and the matrix is ​​regulated, and the problems of high fiber slip hardening coefficient and poor tensile performance in the prior art are solved, and the performance improvement of high ductility concrete is achieved.

CN119569363AActive Publication Date: 2025-03-07SOUTHEAST UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411788239.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Among the existing strain-hardened cement matrix composite materials, there are difficulties in regulating the interface performance between PVA fiber and the matrix, resulting in high fiber slip hardening coefficient, the fiber is easily pulled out during the extraction stage, and the tensile performance is poor.

Method used

The nanospheres are modified with alkali-active red mud-based nanospheres by dispersing and soaking the PVA fibers in the alkali-active red mud slurry, so that the nanospheres grow on the fiber surface and regulate the interface performance between the fiber and the matrix.

Benefits of technology

It effectively reduces the slip hardening coefficient between the fiber and the matrix, prevents the fiber from being pulled out during the extraction stage, and improves the tensile performance of high-ductile concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569363A_ABST
    Figure CN119569363A_ABST
Patent Text Reader

Abstract

The invention discloses an alkali-active red mud-based nanosphere modified fiber and a preparation method and application thereof, non-agglomerated spherical nanoparticles grow on the surface of the modified fiber, and the modified fiber is prepared from the following raw materials: red mud, slag, fly ash, an alkali activator and fiber in a mass ratio of (70-100): (10-30): (10-30): (40-60): (26-30). The red mud is activated by utilizing an exciting agent, the PVA fiber is soaked after the mineral admixture is doped, the alkali-active red mud-based nanospheres grow on the surface of the PVA fiber, and the nanospheres are rich in Ca, Al, Si and other elements, so that the nanospheres can be used for regulating and controlling the interface performance of the high-ductility concrete fiber-matrix; according to the method, the fibers do not need to be coated with multiple layers of materials, the interface performance of the fibers and the matrix can be regulated and controlled, the fibers cannot be damaged, a new thought is provided for resource utilization of the red mud, and the method has the advantages of being low in carbon emission, low in production cost, wide in raw material range, simple in preparation method and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an alkali-activated red mud-based nanosphere modified fiber and a preparation method and application thereof, belonging to the technical field of nanomaterial regulation of fiber-matrix interface performance. Background Art

[0002] As a large solid waste containing a large amount of aluminosilicate substances, the resource utilization of red mud has been one of the key research topics in recent years. Although red mud is an aluminum-rich material, it is mostly inert oxides, so it needs to be activated by alkali. Red mud will form different microstructures after being activated to different degrees, some of which have a greater contribution to specific mechanical properties, providing a basis for the use of red mud in regulating high-performance concrete. This is of practical significance for solving the environmental problems caused by the large-scale accumulation of red mud solid waste and its specific application in civil engineering.

[0003] High Ductility Cementitious Composites (HDCC) is a fiber-reinforced cementitious material with an ultimate elongation greater than 0.5% and an average crack width less than 100 μm. Under tensile load, strain hardening behavior occurs, and cracks expand steadily to form multi-crack cracking. Its excellent crack control ability provides a basis for solving the problem of reflective cracks in the base layer. Based on the guidance of the mesomechanical bridging theory, HDCC can produce multi-crack cracking and strain hardening characteristics. Li et al. from the University of Michigan applied the mesomechanical bridging model design of traditional ECC (Engineering Cement Composites) to HDCC and HDGC with geopolymer as the main raw material, and proved that the design theory is also applicable to HDGC. Therefore, the design of HDGC materials must follow the strain hardening criterion and the fiber bridging law that combines the macroscopic tensile mechanical properties with the pull-out behavior of a single fiber. The calculation of the strength criterion and the energy criterion is based on the single-crack fiber bridging stress σ and the crack opening width δ, thereby establishing the fiber bridging law that combines the macroscopic tensile mechanical properties of HDGC with the pull-out behavior of a single fiber. Whether it is HDCC or HDGC, its excellent crack control ability depends on the bridging effect of the fiber at the crack and the stable expansion of the crack when the stress is transferred between the fiber and the matrix, resulting in multi-crack cracking characteristics and strain hardening behavior. Therefore, the fiber-matrix interface properties are crucial to the tensile properties of the composite material.

[0004] At present, the fibers used in strain-hardening cement-based composite materials are mostly PE fibers and PVA fibers. Since PE fibers are expensive and their long-term mechanical properties decline, PVA fibers are used more. In order to adjust the interface properties between PVA fibers and the matrix, oil is generally applied to the surface of PVA fibers. CN102936848A discloses a modification method of polyvinyl alcohol fibers and a large-volume concrete with high crack resistance. The oil easily enters the matrix, affects the matrix performance, and the process is complicated; CN106045418A discloses a modified polyvinyl alcohol fiber for high-ductility cement-based composite materials, a modification method and a composite material thereof, wherein potassium permanganate is used to oxidize the surface of PVA fibers to make the fiber surface rough and then a layer of hydrophobic material is applied, which will damage the fiber surface and reduce the fiber performance, and the process is complicated; CN108298853A discloses a modification method of polyvinyl alcohol fibers for strain-hardening cement-based composite materials, wherein epoxy resin is used to pre-treat the surface of PVA fibers and then a layer of nanographite powder is applied, but epoxy resin affects the fiber performance, and the process is complicated, the cost is high, and double-layer coating is required. Therefore, it is urgent to develop a modified fiber to effectively reduce the slip hardening coefficient between the fiber and the matrix, avoid the fiber being broken during the pull-out stage, and improve the tensile properties of high-ductility concrete. Summary of the invention

[0005] Purpose of the invention: In view of the above-mentioned problems, the first purpose of the present invention is to provide an alkali-activated red mud-based nanosphere modified fiber, the second purpose of the present invention is to provide a method for preparing the alkali-activated red mud-based nanosphere modified fiber, the third purpose of the present invention is to provide an application of the alkali-activated red mud-based nanosphere modified fiber in the preparation of high ductility concrete, and the fourth purpose of the present invention is to provide a method for regulating the fiber-matrix interface properties of high ductility concrete by utilizing the active red mud-based nanosphere modified fiber, thereby effectively reducing the slip hardening coefficient between the fiber and the matrix, avoiding the fiber from being pulled out during the pull-out stage, and improving the tensile properties of high ductility concrete.

[0006] Technical solution: The present invention discloses an alkali-activated red mud-based nanosphere modified fiber, wherein non-agglomerated spherical nanoparticles grow on the surface of the alkali-activated red mud-based nanosphere modified fiber, and the fiber is made of the following raw materials in the following mass ratio: red mud: slag: fly ash: alkaline activator: PVA fiber (70-100): (10-30): (10-30): (40-600): (26-30), wherein the spherical nanoparticles are alkali-activated red mud-based nanospheres, and the alkali-activated red mud-based nanospheres are obtained by modifying red mud with an alkaline activator.

[0007] Furthermore, the raw materials are prepared in the following mass ratios: red mud: slag: fly ash: alkaline activator: PVA fiber which is 70:15:15:50:26.

[0008] Furthermore, the particle size of the nanoparticles is 1 to 2 nm.

[0009] Furthermore, the fiber is PVA fiber, and the length of the fiber is 8 to 12 mm.

[0010] Furthermore, the red mud is one or more of Bayer process red mud, sintering process red mud or combined process red mud.

[0011] Furthermore, the slag is S95 grade slag or S105 grade slag.

[0012] Furthermore, the fly ash is low calcium class I fly ash or low calcium class II fly ash.

[0013] Furthermore, the alkaline activator is prepared with water glass and NaOH to a modulus of 1.8.

[0014] The method for preparing the alkali-activated red mud-based nanosphere modified fiber of the present invention comprises the following steps:

[0015] (1) red mud, slag and fly ash are mixed, an alkaline activator is added, and the mixture is stirred evenly to obtain a red mud slurry;

[0016] (2) The PVA fibers are evenly dispersed and immersed in the red mud slurry, and then soaked and dried.

[0017] Furthermore, in step (2), the soaking temperature is 25°C to 30°C, and the soaking time is 6 to 8 hours.

[0018] Furthermore, in step (2), the drying temperature is 50 to 60° C., and the drying time is 12 to 24 hours.

[0019] The present invention also includes the use of the alkali-activated red mud-based nanosphere modified fiber in the preparation of high-ductility concrete.

[0020] Furthermore, the alkali-activated red mud-based nanosphere modified fiber of the present invention is added to concrete slurry, poured into a mold, and naturally cured.

[0021] The present invention comprises a method for regulating and controlling the interfacial performance of high-ductility concrete fiber-matrix, which is regulated and controlled by using the alkali-activated red mud-based nanosphere modified fiber of the present invention.

[0022] Principle of the invention: Red mud is a bulk solid waste containing a large amount of aluminosilicate substances. Under the action of an alkali activator, a volcanic ash reaction occurs to form a "spherical" structure with a certain strength. The size of the alkali-activated red mud-based nanosphere structure is observed to be 1-2nm, and it is uniform, oriented, and non-agglomerated. This unique structural property provides a new idea for regulating the fiber-matrix interface performance of high-ductility concrete. From the initial alkali-activated nanosphere molding test results, it can be seen that the number of nanospheres is small when only red mud exists. This is because the silicon and aluminum elements that form the nanospheres are insufficient. Therefore, the silicon and aluminum content of the system can be regulated by adjusting the proportion of mineral admixtures to achieve the purpose of controlling the number of alkali-activated nanospheres and meet the different requirements of high-ductility concrete for fiber-matrix interface performance. When high-ductility concrete is subjected to tensile load, the alkali-activated red mud-based nanospheres that have grown in large quantities on the fiber surface can reduce the slip hardening coefficient between the fiber and the matrix during fiber slip, play a certain degree of lubrication, and thus regulate the tensile ductility.

[0023] The present invention uses red mud as raw material, activates the red mud with an activator, disperses and soaks PVA fibers in red mud slurry to wait for the growth of alkali-active red mud-based nanospheres, the nanospheres are rich in elements such as Ca, Al, Si, etc., and in order to regulate the number of the nanospheres, a mineral admixture is added to provide sufficient raw materials for the growth of the nanospheres, and the number of the alkali-active red mud-based nanospheres can be regulated, so that the nanospheres can be used to regulate the fiber-matrix interface performance of high-ductility concrete; the method of the present invention does not need to coat the fibers with multiple layers of multiple materials, can well regulate the interface performance of the fibers and the matrix, will not damage the fibers themselves, provides a new idea for the resource utilization of red mud, and has the advantages of low carbon emissions, low production cost, a wide range of raw materials, a simple preparation method, and the like. The fiber is modified by the method of the present invention, which has a simple process, low cost, and no need to perform multi-layer treatment on the fiber. The alkali-activated red mud-based nanospheres can be uniformly grown in a single layer on the fiber surface; at the same time, the number of nanospheres can be regulated by adjusting the degree of red mud activation, and the fiber-matrix interface can be regulated on the basis of ensuring the mechanical properties of high-ductility concrete, thereby improving the cracking performance of concrete and improving tensile ductility. Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0024] (1) The method of the present invention does not require multi-layer treatment of the fiber surface, and the alkali-activated red mud-based nanospheres can be uniformly and monolayered on the fiber surface, simplifying the process flow;

[0025] (2) The alkali-activated red mud-based nanospheres of the present invention greatly reduce the slip hardening coefficient between the fiber and the high-ductility concrete matrix, thereby preventing the fiber from being broken during the extraction stage, and will not affect the original physical and mechanical properties of the PVA fiber;

[0026] (3) The present invention uses solid waste red mud as raw material, which can significantly reduce carbon emissions and production costs, and achieve large-scale disposal of solid waste;

[0027] (4) The raw materials of the present invention have a wide range of applications and can be applied to the preparation of composite materials in different industrial production locations;

[0028] (5) The preparation method of the present invention is simple and has high preparation efficiency, which provides a new idea for fiber modification research. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the surface morphology of PVA fiber observed by optical microscope in Example 1;

[0030] Figure 2 This is the morphology of the alkali-active nanospheres on the surface of PVA fiber after activation observed under a microscope in Example 1;

[0031] Figure 3 This is the morphology of the alkali-active nanospheres in the red mud matrix after activation observed under a microscope in Example 1;

[0032] Figure 4 The enlarged morphology and energy spectrum of the alkali-active nanospheres observed under a microscope in Example 1

[0033] Figure 5 The morphology of the alkali-active nanospheres on the surface of PVA fibers mixed with different proportions of mineral admixtures observed under a microscope in Example 3 and Example 5;

[0034] Figure 6 The uniaxial tensile stress-strain curves of Examples 2 to 5 are shown;

[0035] Figure 7 is a load-displacement curve of the fiber being pulled out of the concrete matrix in Example 6;

[0036] Figure 8 This is the change diagram of the sliding hardening coefficient of Example 6. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0038] 1.8 Preparation of modulus alkaline activator:

[0039] (1) Select original liquid sodium silicate water glass (Na2SiO3), with a modulus of 2.43, a solid content of 46.1wt%, and SiO2 and Na2O mass fractions of 29.24% and 12.11% respectively. Weigh 584 portions for later use;

[0040] (2) Select flake NaOH with an analytical purity of 96.8%. Weigh 36 portions for later use;

[0041] (3) Tap water, weigh 123 portions for later use;

[0042] (4) Mix and stir the weighed liquid sodium silicate water glass, flake NaOH and water for 3 minutes until there is no precipitation in the suspension to prepare an activator suspension;

[0043] (5) The activator suspension was allowed to stand for 24 hours at a temperature of 25° C. to obtain a 1.8 modulus alkaline activator.

[0044] Example 1

[0045] (1) Weighing raw materials: 100 parts of Bayer red mud, 60 parts of 1.8 modulus alkaline activator, and 26 parts of PVA fiber;

[0046] (2) premixing the Bayer red mud in a mixer, wherein the mixer blade rotates at a frequency of 140 revolutions per minute;

[0047] (3) adding the alkaline activator to the mixer and stirring until the mixture becomes fluid, stirring at a frequency of 140 rpm for 2 minutes, and then stirring at a frequency of 285 rpm for 1 minute;

[0048] (4) The PVA fibers were evenly dispersed and immersed in the red mud slurry at a temperature of 25° C. for 8 h;

[0049] (5) The treated PVA fibers were taken out and dried in a vacuum drying oven until constant weight was reached. The drying temperature was 60°C and the drying time was 20 h to obtain activated PVA fibers.

[0050] The fiber surface morphology of the PVA fiber, the activated PVA fiber prepared in this example, and the activated red mud matrix remaining in step (6) was observed by optical microscopy. The results are as follows: Figure 1-4 As shown. Figure 1 , 2 3. By comparison, red mud can be activated by alkaline activators and form stable, uniform, directional, non-agglomerated and uniformly sized spherical nanoparticles with a particle size between 1-2nm under certain preparation processes and maintenance systems. Figure 4 From the energy spectrum in the figure, we can see that this alkali-active red mud-based nanosphere mainly contains calcium, silicon, and aluminum. The red mud itself has limited calcium and aluminum content. Therefore, adding different proportions of mineral admixtures can adjust the silicon and aluminum content of the system and generate more alkali-active red mud-based nanospheres. This nanoparticle that grows uniformly on the fiber surface will affect the fiber-matrix interface performance when the high-ductility concrete is subjected to tensile load, play a lubricating role, and provide a basis for improving tensile ductility.

[0051] Example 2

[0052] (1) Weighing raw materials: 70 parts of sintering red mud, 10 parts of S105 grade slag, 20 parts of low calcium grade I fly ash, 50 parts of 1.8 modulus alkaline activator, and 26 parts of PVA fiber;

[0053] (2) premixing sintered red mud, slag and fly ash in a mixer, wherein the mixer blade rotates at a frequency of 140 revolutions per minute;

[0054] (3) adding the alkaline activator to the mixer and stirring until the mixture becomes fluid, stirring at a frequency of 140 rpm for 2 minutes, and then stirring at a frequency of 285 rpm for 1 minute;

[0055] (4) The PVA fibers were evenly dispersed and immersed in the red mud slurry at a temperature of 25°C for 6 h;

[0056] (5) The treated PVA fiber was taken out and dried in a vacuum drying oven until constant weight was reached. The drying temperature was 50°C and the drying time was 18 h to obtain modified PVA fiber.

[0057] (6) The modified PVA fiber treated in step (5) was added to concrete (1240 parts of ordinary Portland cement, 372 parts of ordinary river sand, 372 parts of water, 3.6 parts of water reducer, and 0.7 parts of thickener) to prepare a high-ductility concrete slurry material.

[0058] The high ductility concrete paste material obtained in this embodiment was tested for relevant properties. The test results are shown in Table 1. The uniaxial tensile stress-strain curve of the material is shown in Figure 6 As shown in (A-1).

[0059] Example 3

[0060] The preparation process is the same as in Example 2, specifically as follows:

[0061] (1) Weighing raw materials: 70 parts of combined red mud, 15 parts of S105 grade slag, 15 parts of low calcium grade II fly ash, 50 parts of 1.8 modulus alkaline activator, and 26 parts of PVA fiber;

[0062] (2) premixing the combined red mud, slag and fly ash in a mixer, wherein the mixer blade rotates at a frequency of 140 revolutions per minute;

[0063] (3) adding the alkaline activator to the mixer and stirring until the mixture becomes fluid, stirring at a frequency of 140 rpm for 2 minutes, and then stirring at a frequency of 285 rpm for 1 minute;

[0064] (4) The PVA fibers were evenly dispersed and immersed in the red mud slurry at a temperature of 27° C. for 8 h;

[0065] (5) The treated PVA fiber was taken out and dried in a vacuum drying oven until constant weight was reached. The drying temperature was 55°C and the drying time was 20 h to obtain modified PVA fiber.

[0066] (6) The modified PVA fibers treated in step (5) are added to concrete (the materials and amounts are consistent with those in Example 2) to prepare a high-ductility concrete slurry material.

[0067] The surface morphology of the modified PVA fiber prepared in this example was observed by optical microscope. Figure 5 As shown in A.

[0068] The high ductility concrete paste material obtained in this embodiment was tested for relevant properties. The test results are shown in Table 1. The uniaxial tensile stress-strain curve of the material is shown in Figure 6 As shown in (A-2).

[0069] Example 4

[0070] The preparation process is the same as in Example 2, specifically as follows:

[0071] (1) Weighing raw materials: 70 parts of Bayer red mud, 20 parts of S95 grade slag, 10 parts of low calcium grade II fly ash, 50 parts of 1.8 modulus alkaline activator, and 26 parts of PVA fiber;

[0072] (2) premixing Bayer red mud, slag and fly ash in a mixer, wherein the mixer blade rotates at a frequency of 140 revolutions per minute;

[0073] (3) adding the alkaline activator to the mixer and stirring until the mixture becomes fluid, stirring at a frequency of 140 rpm for 2 minutes, and then stirring at a frequency of 285 rpm for 1 minute;

[0074] (4) The PVA fibers were evenly dispersed and immersed in the red mud slurry at a temperature of 30 °C for 6 h.

[0075] (5) taking out the treated PVA fiber, and drying it in a vacuum drying oven until constant weight, the drying temperature is 60° C., and the drying time is 24 h, to obtain modified PVA fiber;

[0076] (6) The modified PVA fibers treated in step (5) are added to concrete (the materials and amounts are consistent with those in Example 2) to prepare a high-ductility concrete slurry material.

[0077] The high ductility concrete paste material obtained in this embodiment was tested for relevant properties. The test results are shown in Table 1. The uniaxial tensile stress-strain curve of the material is shown in Figure 6 Example 5

[0078] The preparation process is the same as that of Example 4, except that low-calcium grade II fly ash is not used, and 30 parts of S95 grade slag are used to replace 20 parts of S105 grade slag and 10 parts of low-calcium grade II fly ash, as follows:

[0079] (1) Weighing raw materials: 70 parts of Bayer red mud, 30 parts of S95 grade slag, 50 parts of 1.8 modulus alkaline activator, and 2 parts of PVA fiber;

[0080] (2) premixing the Bayer red mud and slag in a mixer, wherein the mixer blade rotates at a frequency of 140 revolutions per minute;

[0081] (3) adding the alkaline activator to the mixer and stirring until the mixture becomes fluid, stirring at a frequency of 140 rpm for 2 minutes, and then stirring at a frequency of 285 rpm for 1 minute;

[0082] (4) The PVA fibers were evenly dispersed and immersed in the red mud slurry at a temperature of 30 °C for 6 h.

[0083] (5) taking out the treated PVA fiber, and drying it in a vacuum drying oven until constant weight, the drying temperature is 60° C., and the drying time is 24 h, to obtain modified PVA fiber;

[0084] (6) The modified PVA fibers treated in step (5) are added to concrete (the materials and amounts are consistent with those in Example 2) to prepare a high-ductility concrete slurry material.

[0085] The surface morphology of the modified PVA fiber prepared in this example was observed by optical microscope. Figure 5 As shown in B. Figure 5 It is known that after treating the fiber with different proportions of mineral admixtures, the number of alkali-active red mud-based nanospheres on the fiber surface is also different. It should be pointed out that since the growth of alkali-active nanospheres requires a certain amount of calcium, the calcium content of fly ash is low and cannot provide sufficient raw materials for the growth of nanospheres. Therefore, the embodiment using fly ash alone is not discussed.

[0086] The relevant properties of the high ductility concrete paste material obtained in Examples 2-5 were tested. The test results are shown in Table 1. The uniaxial tensile stress-strain curve of the material is shown in Figure 6 As shown in (A-4).

[0087] Table 1 Uniaxial stretching data of Example 2-Example 5

[0088]

[0089] From Table 1 and Figure 6Comparative analysis shows that Example 3 has the best uniaxial tensile ductility, which is because this ratio has the best modification effect on the fiber, effectively reducing the slip hardening coefficient of the fiber during the extraction process from the concrete, and effectively improving the tensile ductility while ensuring that the fiber is not broken. Example 5 has the most alkali-activated red mud-based nanospheres, but the ductility is not the best, indicating that the larger the amount of slag (providing Ca), the better, and it should be matched with fly ash (providing Al and Si) in a suitable ratio to be more conducive to the regulation of fiber-matrix interface performance.

[0090] Example 6

[0091] The fibers with different numbers of alkali-activated red mud-based nanospheres grown on the surface in Examples 2 to 5 were subjected to a load displacement test for single-filament pullout in a high-ductility concrete matrix. The single modified PVA fibers prepared in Examples 2 to 5 were respectively inserted into the hardened slurry. The test method was referred to CN104807749A. The test results are shown in FIG. Figure 7 shown.

[0092] The fiber-matrix interface parameters in this example are statistically analyzed and shown in Table 2. The variation law of the sliding hardening coefficient under different red mud activation degrees is as follows: Figure 8 shown.

[0093] Table 2 Fiber-matrix interface parameters of Example 6

[0094]

[0095] It can be seen from Table 2 that the increase in the number of nanospheres will lead to a significant decrease in the slip hardening coefficient. Combined with the changing trend of tensile ductility, the PSH index of tensile ductility calculated by three parameters shows that the change in the slip hardening coefficient has a greater impact on the fiber-matrix interface. This is because the alkali-activated red mud-based nanospheres on the fiber surface play a lubricating role in the fiber extraction process.

[0096] The method described in the present invention uses nanospheres generated from alkali-activated red mud to regulate the fiber-matrix interface performance of high-ductility concrete. First, the red mud is activated to prepare alkali-activated red mud-based nanospheres in the matrix. At this time, the number of nanospheres is relatively small. Secondly, different proportions of mineral admixtures are added to change the calcium and aluminum content of the system to regulate the number of alkali-activated nanospheres generated. The main material of the cementitious system, regulating the proportion of mineral admixtures affects the degree of activation of the system, and forms activated red mud structures with different numbers and different morphologies on the fiber surface. The alkali-activated nanospheres can reduce the slip hardening coefficient of the fiber-matrix interface when the high-ductility concrete is subjected to tensile load, thereby improving the tensile ductility. At the same time, the addition of mineral admixtures can change the silicon and aluminum content in the matrix, thereby affecting the number of alkali-activated red mud-based nanospheres and directionally regulating the tensile ductility.

[0097] It should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any combination or equivalent transformation made on the basis of the above embodiments shall fall within the protection scope of the present invention.

Claims

1. An alkali-activated red mud-based nanosphere modified fiber, characterized in that: The alkali-activated red mud-based nanosphere modified fiber has non-agglomerated spherical nanoparticles grown on its surface, and is made of the following raw materials in the following mass ratios: red mud: slag: fly ash: alkaline activator: fiber (70-100): (10-30): (10-30): (40-60): (26-30).

2. The alkali-activated red mud-based nanosphere modified fiber according to claim 1, characterized in that: The method comprises the following raw materials in a mass ratio: red mud: slag: fly ash: alkaline activator: PVA fiber of 70:15:15:50:

26.

3. The alkali-activated red mud-based nanosphere modified fiber according to claim 1, characterized in that: The particle size of the nanoparticles is 1-2 nm, the fibers are PVA fibers, and the length of the fibers is 8-12 mm.

4. The alkali-activated red mud-based nanosphere modified fiber according to claim 1, characterized in that: The red mud is one or more of Bayer process red mud, sintering process red mud or combined process red mud.

5. The alkali-activated red mud-based nanosphere modified fiber according to claim 1, characterized in that: The slag is S95 grade ground granulated blast furnace slag or S105 grade ground granulated blast furnace slag; the fly ash is low calcium grade I fly ash or low calcium grade II fly ash.

6. The alkali-activated red mud-based nanosphere modified fiber according to claim 1, characterized in that: The alkaline activator is prepared with water glass and NaOH to a modulus of 1.

8.

7. The method for preparing the alkali-activated red mud-based nanosphere modified fiber according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) red mud, slag and fly ash are mixed, an alkaline activator is added, and the mixture is stirred evenly to obtain a red mud slurry; (2) The PVA fibers are evenly dispersed and immersed in the red mud slurry, and then soaked and dried.

8. The method for preparing alkali-activated red mud-based nanosphere modified fibers according to claim 6, characterized in that: In step (2), the soaking temperature is 25°C to 30°C, the soaking time is 6 to 8 hours, the drying temperature is 50 to 60°C, and the drying time is 12 to 24 hours.

9. Use of the alkali-activated red mud-based nanosphere modified fiber according to any one of claims 1 to 6 in the preparation of high-ductility concrete.

10. A method for regulating high ductility concrete fiber-matrix interface performance, characterized in that: The alkali-activated red mud-based nanosphere modified fiber according to any one of claims 1 to 6 is used for regulation.

Citation Information

Patent Citations

  • Method for modifying polyvinyl alcohol fibers and mass concrete with high crack resistance

    CN102936848A

  • Modified polyvinyl alcohol fibers for high-ductility cement-based composite material, modifying method and composite material prepared from modified polyvinyl alcohol fibers

    CN106045418A

  • Modification method of polyvinyl alcohol fiber for strain-hardening cement-based composite material

    CN108298853A

  • Cement-based composite and preparation method thereof

    CN106278026A

  • Surface-modified steel fiber, modification method and concrete based on steel fiber

    CN117800641A